Microstructural characterisation of dry mixed rubberised asphalt mixtures - Abdul Hassan, Norhidayah (Elsevier Ltd., 2015)
This study characterises the microstructural properties of Hot Rolled Asphalt (HRA60/20) modified with different percentages and sizes of crumb rubber using dry process method. A number of specimens from five different mixtures were scanned using X-ray Computed Tomography (CT) together with image analysis technique to evaluate the effects of rubber size and concentration on the voids formation and rubber distribution within the gyratory compacted specimens. A set of procedures for processing and extracting the voids and crumb rubber was established in thresholding the region of interest. Results showed that the increase in the rubber content and rubber sizes affect the rubber distribution and air voids properties within the compacted asphalt mixture. The rubber particles affect the effectiveness of compaction and tend to cause the large air voids to scatter randomly into smaller sizes during compaction. This finding is more pronounced in specimen with fine rubber, whereas for the control mixture, the air voids are more localised and large sized.